Telehealth acceptance among health workers as a digital health strategy - Gita, Anggi Putri Aria; Pinto, Sufina; Goncalves, Livia Babo; Prasastin, Oliva Virvizat; Soares, Domingos (Universitas Gadjah Mada, 2025)
Purpose: This study analyzes the acceptance of telehealth among health workers at Gondangrejo Community Health Center, Indonesia, and at Sentro De Saude Becora Timor Leste, as a digital health strategy. Methods: This study employed an analytical observational research design with a cross-sectional approach using the Technology Acceptance Model questionnaire. The sample in this study comprised 30 health workers from the Gondangrejo Health Center in Indonesia and the Sentro De Saude Becora in Timor Leste. Data analysis and statistical tests used Pearson correlation. Results: There was a positive and significant relationship between perceived ease of use and perceived usefulness (p-value < 0.001; r=0.972), perceived usefulness and attitude toward using (p-value=0.015; r=0.359), perceived ease of use and attitude toward using (p-value=0.042; r=0.305), attitude toward using and behavioral intention to use (p-value < 0.001; r = 0.888), perceived usefulness and behavioral intention to use (p-value < 0.016; r=0.356), behavioral intention to use and actual system use (p-value < 0.022; r=0.342). Conclusion: Acceptance of telehealth by healthcare workers is influenced by perceived usefulness, perceived ease of use, attitude toward using, behavioral intention to use, and actual system use.